2016
DOI: 10.4137/nmi.s39764
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal-encapsulated Ascorbic Acid: Influence on Vitamin C Bioavailability and Capacity to Protect against Ischemia–Reperfusion Injury

Abstract: Intravenous administration of vitamin C has been shown to decrease oxidative stress and, in some instances, improve physiological function in adult humans. Oral vitamin C administration is typically less effective than intravenous, due in part to inferior vitamin C bioavailability. The purpose of this study was to determine the efficacy of oral delivery of vitamin C encapsulated in liposomes. On 4 separate randomly ordered occasions, 11 men and women were administered an oral placebo, or 4 g of vitamin C via o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 44 publications
2
50
0
1
Order By: Relevance
“…Standardowo zalecana suplementacja witaminą C to dawka od 100 do 1000 mg/dzień w postaci tabletek powlekanych [6,49]. Przy zaawansowanych postaciach szkorbutu polecana jest forma liposomalna, charakteryzująca się zwiększoną wchłanialnością [48]. Przy stanach zapalnych pochwy zaleca się suplementację dopochwową w dawce 250 mg/dzień [49].…”
Section: Zastosowanie Witaminy Cunclassified
“…Standardowo zalecana suplementacja witaminą C to dawka od 100 do 1000 mg/dzień w postaci tabletek powlekanych [6,49]. Przy zaawansowanych postaciach szkorbutu polecana jest forma liposomalna, charakteryzująca się zwiększoną wchłanialnością [48]. Przy stanach zapalnych pochwy zaleca się suplementację dopochwową w dawce 250 mg/dzień [49].…”
Section: Zastosowanie Witaminy Cunclassified
“…The alternative route, i.e. oral vitamin C, however, has less bioavailability than infusion (Davis et al 2016). Vitamin C is a chemically active and highly unstable agent against environmental factors such as temperature, pH, light, and oxygen, which shows wide instability in aqueous solutions (Matos-Jr et al 2015, Alvim et al 2016, Fong et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Liposomal vitamin C produced higher blood levels of vitamin C than those elicited by unencapsulated vitamin C, but less than that following intravenous vitamin C administration (Figure 2). Moreover all treatments, except placebo, provided equal protection from ischemia-reperfusion injury [21].…”
Section: Liposomal Technology and Nutritionmentioning
confidence: 99%
“…The authors reported that the highest peak plasma level (~ 400 uM/L) was achieved with 36 g, peaking after ~5-6 hours post-ingestion. A more recent study investigated the efficacy of liposomal vitamin C and its effects on ischemia-reperfusion injury [21]. Oral placebo or 4 g of vitamin C via oral unencapsulated, oral liposomal, or intravenous delivery were administered.…”
Section: Liposomal Technology and Nutritionmentioning
confidence: 99%